2020
DOI: 10.1073/pnas.2002759117
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen manipulation of chloroplast function triggers a light-dependent immune recognition

Abstract: In plants and animals, nucleotide-binding leucine-rich repeat (NLR) proteins are intracellular immune sensors that recognize and eliminate a wide range of invading pathogens. NLR-mediated immunity is known to be modulated by environmental factors. However, how pathogen recognition by NLRs is influenced by environmental factors such as light remains unclear. Here, we show that the agronomically important NLR Rpi-vnt1.1 requires light to confer disease resistance against races of the Irish potato famine pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 37 publications
2
50
0
Order By: Relevance
“…Light is required for expression of full-length tomato and potato glycerate 3kinase (GLYK) transcripts encoding a chloroplast transit sequence. AVRvnt1 binds to this chloroplast-targeting sequence and activates resistance (independent of GLYK kinase activity), impairing accumulation of GLYK in both total and chloroplast fractions of potato (Gao et al, 2020). This is somewhat analogous to the TMV N-NRIP1 interaction described above (Caplan et al, 2008), but in this case AVRvnt1 intercepts GLYK's trafficking to the chloroplast, the depletion of which (probably via proteasomal degradation) is indirectly sensed by Rpi-vnt1.1 activating ETI (Fig.…”
Section: Emerging Examples Of Indirect Transcriptional Modulation Of mentioning
confidence: 77%
See 1 more Smart Citation
“…Light is required for expression of full-length tomato and potato glycerate 3kinase (GLYK) transcripts encoding a chloroplast transit sequence. AVRvnt1 binds to this chloroplast-targeting sequence and activates resistance (independent of GLYK kinase activity), impairing accumulation of GLYK in both total and chloroplast fractions of potato (Gao et al, 2020). This is somewhat analogous to the TMV N-NRIP1 interaction described above (Caplan et al, 2008), but in this case AVRvnt1 intercepts GLYK's trafficking to the chloroplast, the depletion of which (probably via proteasomal degradation) is indirectly sensed by Rpi-vnt1.1 activating ETI (Fig.…”
Section: Emerging Examples Of Indirect Transcriptional Modulation Of mentioning
confidence: 77%
“…Chloroplast lipids and cROS appear to be central to generation of SAR inducing signal(s) following ETI‐activated HR (Wendehenne et al ., 2014; Shine et al ., 2019), supported by the SAR‐deficient phenotypes of fatty acid desaturase ( sfd2 ; SUPPRESSOR OF FATTY ACID DESATURASE DEFICIENCY2) mutants. The chloroplast galactolipid mutants mgd1 and dgd1 ( monogalactosyl synthase 1 , digalactosyl synthase 1 ), responsible for monogalactosyldiacylglycerol (MGDG) and digalactosyldiacylglycerol (DGDG) synthesis respectively, function nonredundantly in initial SAR signal perception (Gao et al ., 2014; Shah et al ., 2014). As noted above, ETI‐generated ROS modify fatty acids on chloroplast galactolipids leading to rapid JA accumulation (Andersson et al ., 2006; Zoeller et al ., 2012).…”
Section: Cros In Immunity and Insights From Disruption Of Chloroplastmentioning
confidence: 99%
“…Moreover, co-expression of Avrvnt1 and Rpi-vnt1 or single Avrvnt1 failed to induce HR in S. pinnatisectum, suggesting that specific interacting proteins are needed for Avrvnt1-Rpi-vnt1 recognition. As Gao C et al pointed out [31], glycerate 3-kinase (GLYK) is involved in activation of of Rpi-vnt1. Similarly, Avrblb1 and Rpi-blb1 only triggered typical HR in N. benthamiana but not in Arabidopsis thaliana, indicating that species-specific interactors are involved in cell death induction [32].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been reported that both pathogen-associated molecular pattern (PAMP) -triggered immunity (PTI) and effector-triggered immunity (ETI) contribute to the resistance response to rice blast (Boller and Felix 2009 ), and NLR -mediated immunity is known to be modulated by many environmental factors such as light (Gao et al 2020 ). In the present study, nine SEP between Piz-t-KJ201 and NPB-KJ201 were found, especially green-yellow module, in which the photosystem plays a vital role.…”
Section: Discussionmentioning
confidence: 99%